Gambaran Hematologi pada Rusa Timor (Cervus timorensis) - Yanse Yane Rumlaklak; Novianti Neliyani Toelle (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Timorensis deer, an endangered species, is one of the native wildlifes in Nusa Tenggara Timur Province. Therefore, it is important to protect the Timorensis deer population in this province. The purpose of this study is to determine haematology value of the Timor deer (Cervus timorensis). Blood samples were taken from four captive deers, owned by Kupang Forestry Research Institute, in Sonbai which are clinically health based on the general physical examination namely temperature and heart frequence. Hematological examination includes the number of blood cells, hemoglobin concentration, hematocrit value, erythrocyte indices, and the calculation of leukocytes. Results of this study showed that there were significant increasing the number of leukocytesis 8.42x103/μl and erythrocytes index is 8.24x106/μl.